Beta blocker therapy in recipients of twin-to-twin transfusion syndrome. Issue 5 (24th September 2019) - Gruendler, Kerstin; Schwarz, Christoph E; Lorenz, Laila; Poets, Christian F; Franz, Axel R
Abstract : Recipients of severe twin-to-twin transfusion syndrome (TTTS) may suffer from low cardiac output caused by myocardial hypertrophy and sudden postnatal drop in preload. Our hypothesis was that selective beta-1 adrenergic blockers improve cardiac function in TTTS recipients with left ventricular outflow tract obstruction. We analysed data from two TTTS recipients treated with esmolol/metoprolol. Despite intense circulatory support, both patients showed severe hypotension and tachycardia before therapy. Echocardiographic findings included hypertrophic ventricles with thickened intraventricular septum, reduced aortic valve velocity time integral (AV-VTI), left ventricular outflow tract obstruction and collapsing ventricles in systole. Beta blocker improved blood pressure as well as AV-VTI, which served as a surrogate parameter for left ventricular stroke volume, reduced heart rate and need for circulatory support. In conclusion, beta blockade may improve left ventricular function in TTTS recipients with low cardiac output due to myocardial hypertrophy.